The Influence Of Innovation And Product Quality To Power Competition Product In Kulumanu Tangerang City Coffee - Sukamto, MD; Sugara, Asep (EMaBi: Ekonomi Dan Manajemen Bisnis, 2025)
The study was carried out with the aim of finding out and explaining the influence of innovation products and quality products to labor competition products in Kulumanu Kopi which is one of the coffee shops in Tangerang City. The research method used is a quantitative method with an associative type that explains the relationship between innovation variables. products and variable quality of products for energy competition products that have been produced in Kulumanu Kopi, Tangerang City. Data analysis uses correlation analysis, determination, and regression, where the data source is the respondents' answers to the questionnaire they have answered, with a sample size of 100 people. This study resulted in an explanation that the relationship between innovation products (X1) and quality products (X2) together with the competition products Power (Y) was R YX1X2 = 0.952 and showed a very strong level of relationship. Meanwhile, the variable of the ability of the size of the innovation product and the variable of the product quality for the Power competition product was 90.63%. Meanwhile, the relationship between the innovation product variable and the product quality variable with the Energy competition product is positive because the innovation product improvement variable and the quality product variable will be followed by an increase in the power competition product value variable that meets the linear regression line equation Y = 1.153 + 0.363X 1 + 1.319X2. This research produces recommendations to Kulumanu Kopi as a coffee shop businessman to conduct periodic evaluations related to product innovation and product quality variables and product competitiveness, so that all changes to the third variable can be quickly anticipated, in addition to the adaptive herus business to technology development in the digital business line and collaboration with e-commerce.